PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KENAKALAN SISWA DI SMA NEGERI 1 MAJA - Salsabiila Syahrani Amalia Sukmana; Ari Prasetyoaji; Astri Setiawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Student delinquency is a form of juvenile delinquency committed in the student category and occurs in the school environment. Where student delinquency occurs due to a violation of the rules set at achool. This study aims to determine how the role of the Guidance and Counseling teacher in overcoming student delinquency that occurs in SMA Negeri 1 Maja. The research method used is qualitative method. The primary source of this research is the Guidance and Counseling Teacher while the secondary source is student affairs and the student concerned. The sampling technique used is purposive sampling. The research instrument used is an interview guide.based on the result of the study, it is found that there are forms of student delinquency in SMA Negeri 1 Maja in the form of being late for school, skipping school or alfa or without information, making fake letters not from parents, jumping fences, and smoking. It can be concluded that the student delinquency, namely by reminding related to the point system that is enforces and what the consequences are and coubleing services are carried out to help students overcome obstacles in themselves.